Naphthyl substituted triphenylamine derivatives as hole transporting materials for efficient red PhOLEDs. (March 2019) - Krucaite, Gintare; Volyniuk, Dmytro; Simokaitiene, Jurate; Grigalevicius, Saulius; Lin, Chun-Han; Shao, Chang-Min; Chang, Chih-Hao
Abstract: Naphthyl substituted triphenylamine and its derivatives with bromine atoms were synthesized and investigated. The respective glass transition temperatures of the materials were estimated to be in a range 65–137 °C, which can provide morphologically-stable amorphous films for applications in organic light emitting diodes. The compounds possess adequate ionization potentials (5.5–5.75 eV), high hole drift mobilities (>10 −3 cm 2 /V·s) and suitable triplet energies (∼2.4 eV), which make them suitable hole transporting materials for use in red phosphorescent organic light-emitting diodes. A superior peak efficiency of 17.9% (31.4 cd/A and 26.9 lm/W) was achieved in a device having hole transporting layer of tris[4-(1-naphthyl)phenyl]amine. Furthermore, the device gave efficiencies of 17.7% and 16.6% recorded at luminance levels of 10 2 and 10 3 cd/m 2 . The efficiency drop from the maximum to the value recorded at the luminance of 10 3 cd/m 2 for the device was only 7%. Highlights: Naphthyl substituted triphenylamine based elctroactive materials were synthesized. The hole transporting materials possess adequate ionization potentials and triplet energies. Red phosphorescent PhOLEDs using the hole transporting materials were formed. Peak external quantum efficiencies of the devices reached 17.9%.